Palmitoylated claudin7 captured in glycolipid-enriched membrane microdomains promotes metastasis via associated transmembrane and cytosolic molecules - Thuma, Florian; Heiler, Sarah; Zöller, Margot (OncoTarget, 2016)
In epithelial cells claudin7 (cld7) is a major component of tight junctions, but is also recovered from glycolipid-enriched membrane microdomains (GEM). In tumor cells, too, cld7 exists in two stages. Only GEM-located cld7, which is palmitoylated, promotes metastasis. Searching for the underlying mechanism(s) revealed the following., The metastatic capacity of the rat pancreatic adenocarcinoma cell line ASML is lost by a knockdown (kd) of cld7 and is not regained by rescuing cld7 with a mutated palmitoylation site (cld7mPalm). ASML-cld7kd and ASML-cld7mPalm cells show reduced motility and invasiveness. This is due to cld7, but not cld7mPalm associating with α6β4, ezrin, uPAR and MMP14, which jointly support motility and invasion. Palmitoylated cld7 also is engaged in drug resistance by repressing Pten, allowing activation of the antiapoptotic PI3K/Akt pathway. An association of cld7mPalm with the major Pten phosphorylating kinases does not restore apoptosis resistance as phosphorylated Pten is not guided towards GEM to compete with non-phosphorylated Pten. The pathway whereby palmitoylated cld7 supports expression of several EMT genes and nuclear translocation of EMT transcription factors remains to be unraveled. An association with Notch, reduced in ASML-cld7mPalm cells, might be the starting point. Finally, GEM-located, palmitoylated cld7 associates with several components of vesicle transport machineries engaged in exosome biogenesis., Taken together, prerequisites for cld7 acting as a cancer-initiating cell marker are GEM location and palmitoylation, which support a multitude of associations and integration into exosomes. The latter suggests palmitoylated cld7 contributing to message transfer via exosomes.
Gesehen am 09.09.2019